Dampak Paparan Gas Hidrogen Sulfida (H2S) Terhadap Kadar Gula Darah Pada Pekerja Pabrik Crumb Rubber Di Kota Palembang Sumatera Selatan - Ferly Oktriyedi; Irfannuddin Irfannuddin; Ngudiantoro Ngudiantoro; M. Hatta Dahlan (Sanitasi: Jurnal Kesehatan Lingkungan, 2021)
Hydrogen sulfide (H2S) is one of the pollutants in the air. One of the industries that cause H2S odor is the natural rubber industry. Exposure to H2S has an impact on increasing blood sugar levels. High blood sugar levels can lead to diabetes. Diabetes mellitus can increase risks such as myocardial infarction, stroke, kidney failure, lower extremity amputation and vision loss. Based on this, the authors are interested in studying the impact of exposure to H2S gas on blood glucose levels in crumb rubber factory workers in the city of Palembang. This study is a cross-sectional analysis. The study was conducted at the crumb rubber factory in Palembang City in March 2020. The sampel this study with a total of 215 workers. Data analysis using chi square with p <0.05. The results of the analysis concluded that there was no relationship between age (pV=0.758), gender (pV=0.532), smoking (pV=1,000), body mass index (pV=0.571), exposure to H2S gas (pV=0.772) with blood glucose levels. This is probably because the main role of H2S in the pancreas is to protect pancreatic B cells and regulate insulin secretion. H2S can protect pancreatic b cells in the following three ways: (1) reducing ROS production; (2) inhibits the expression of thioredoxin binding protein-2-a redox protein associated with diabetes that promotes apoptosis; and (3) increased GSH content, all of which reduce oxidative stress damage.